ENGLISH HYPONYMS IN SPEECH - Алєксєєва, Наталія (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
Nowadays the specificity of onyms in speech is one of the most interesting and, at the same time, complex issues of modern onomastic research. The importance of the study is determined by the need for a comprehensive analysis of the functioning of official hipponyms in written and spoken language. The object of the research are the official horse names in English. The subject of the investigation are the peculiarities of the functioning of hipponyms in the written and oral speech. The purpose of this article is to analyse the peculiarities of the hipponyms in oral (sports discourse) and written (newspaper discourse) speech. The research material was selected from the English media, including electronic magazines and commercial websites, devoted to the events of the equestrian world, as well as from the horse racing sport commentaries, taken from «YouTube». Such methods of the investigation as descriptive and functional were used in the research. Results. The choice of newspaper and sports discourses as the main centers for the functioning of official hipponyms in written and spoken language, respectively, derives from the fact that horse names are used more often by journalists in informational and analytical articles and by commentators directly during the horse race. As a result of the analysis of newspaper articles, we established the main feature of the official hipponyms in the newspaper discourse: in order to influence the reader the substitution of the official name with the nickname is made. Thus, nickname serves as a substitute for the official horse name and is often more commonly known to the public as the name of a horse, than its official name. That`s why nicknames are widely represented in the speech practice of newspaper discourse. It is also expected that the horse name will not only conform to the horse's appearance and personality, but will also sound good when spoken out by the announcer at the competition. Because of this, the owners try to be creative in forming the name, taking into account further active functioning of the names in oral speech. Thus, the principle of deviating from language norms is often used in creation of a horse name.